Psikoedukasi “Bidan Cerdas” untuk Menurunkan Stigma terhadap Orang dengan HIV/AIDS (ODHA) - Adhesatya Ningsih Moodoeto; Esti Hayu Purnamaningsih (Faculty of Psychology, Universitas Gadjah Mada, 2017)
Lack of knowledge about HIV /AIDS makes people including health workers stigmatize people living with HIV (PLWHA). It has a negative impact on PLWHA because of the constraints of quality of service, lowering of health, the reluctance of VCT, and non-compliance of ARVs. The aim of this research to reduce the stigma of midwives against PLWHA through psychoeducation program of